Exportación de loción corporal de sacha inchi al mercado colombiano - Gallori Salazar, María Lucía (2016)
This work develops an exportation plan of body lotion to Bogota, Colombia, based in raw materials from the Peruvian biodiversity, such as the sacha Inchi organic plant. This business will trade this product througgh BIOPERU NATURAL PRODUCTS S.A.C. Company.